CCM and DCM analysis of quasi-z-source inverter - Xuan, J.; Khan, K.; Law, Kah Haw; Qin, W.; Dahidah, M. (2018)
© 2017 IEEE. This paper presents an analysis of a quasi-Z-source inverter (qZSI) operating in continuous conduction mode (CCM) and discontinuous conduction mode (DCM). The boundary between CCM and DCM is discovered and technique to avoid qZSI being operated in DCM is also discovered. The analysis concluded an equation that provides the minimum inductor current and the inductance before qZSI enters DCM. Additionally, the relationship between input and DC-link voltages in DCM is also presented with valid mathematical derivation. A qZSI model is being simulated using MATLAB/SIMULINK® to verify the proposed technique. The simulated results meet the analysis results very well. The design of qZSI for application like photovoltaic (PV), wind power and distributed generations (DG) can be achieved with broad versatility.